2009
DOI: 10.1002/yea.1738
|View full text |Cite
|
Sign up to set email alerts
|

Outward electron transfer by Saccharomyces cerevisiae monitored with a bi‐cathodic microbial fuel cell‐type activity sensor

Abstract: A Janus head-like bi-cathodic microbial fuel cell was constructed to monitor the electron transfer from Saccharomyces cerevisiae to a woven carbon anode. The experiments were conducted during an ethanol cultivation of 170 g/l glucose in the presence and absence of yeast-peptone medium. First, using a basic fuel-cell type activity sensor, it was shown that yeast-peptone medium contains electroactive compounds. For this purpose, 1% solutions of soy peptone and yeast extract were subjected to oxidative conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…Electron shuttles or mediators can also transfer electron from the cathode to the anode and result in electron recycling. It has recently been shown with yeast, for example, that peptone and yeast extract contain compounds that act as electron shuttles or mediators (Ducommun et al, 2010). Doong and Schink (2002) also reported that the amino acid cysteine (abundant in BSA) could function as an electron shuttle between G. sulfurreducens and Fe(III) oxides.…”
Section: Electron Recyclingmentioning
confidence: 98%
“…Electron shuttles or mediators can also transfer electron from the cathode to the anode and result in electron recycling. It has recently been shown with yeast, for example, that peptone and yeast extract contain compounds that act as electron shuttles or mediators (Ducommun et al, 2010). Doong and Schink (2002) also reported that the amino acid cysteine (abundant in BSA) could function as an electron shuttle between G. sulfurreducens and Fe(III) oxides.…”
Section: Electron Recyclingmentioning
confidence: 98%
“…3). S. cerevisiae was added as a reference organism because of the results reported for that yeast by Ducommun et al (2010) and Halme and Zhang (1995). A. adeninivorans and S. cerevisiae performed differently in the mediator-less MFC.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of reports support the idea that electron transfer from the cell to the electrode is by some kind of direct contact between the cell and the electrode. Ducommun et al (2010) constructed a dual cathode and dual anode MFC. The anode A had contact with the cells in a glucose water medium whereas anode B was separated from the cells by dialysis membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Because methane production was very low in these tests, a low r cat value in our tests was not due to hydrogenotrophic microorganisms. It was shown recently that electron shuttles or mediators (such as peptone, yeast extract-containing compounds and the amino acid cysteine) can also transfer electrons from the cathode to the anode, resulting in electron recycling [36,37]. The result of electron recycling is a low cathodic hydrogen recovery rate.…”
Section: Hydrogen Recovery and Energy Efficiencymentioning
confidence: 98%